Survey of Interest, Level of Knowledge and Student Learning Outcomes During the Covid-19 Pandemic - Firmamsyah , Julyant Exccel; Basuki, Basuki (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This study aims to determine interest, level of PJOK knowledge, and learning outcomes of Widjaya Ngoro Vocational School students during the Covid-19 pandemic. This research was motivated by a change in the learning process which was initially carried out face-to-face and changed to online learning. The type of research used is descriptive quantitative using survey methods. The population of this study was grade 11 students. The sampling technique in this study was carried out by means of total sampling and the sample data used were 97 students. While the data collection technique used in the study was a questionnaire or questionnaire with the research instrument using a closed questionnaire through the preparation of answer choices. The validation technique in this study uses construct validity testing. The data analysis technique used is univariant analysis. The results of the research from 97 respondents showed that students' interest was low (52.6%), the knowledge level of PJOK had high knowledge (55.7%), and student learning outcomes were relatively high (52.6%). In conclusion, students lack interest in the online learning process, have high knowledge, and high learning outcomes. After conducting this research, the authors provide suggestions for further developing the online learning process to increase student interest and obtain higher learning outcomes.